Introduction to Cryptography - Padhye, Sahadeo; Sahu, Rajeev Anand; Saraswat, Vishal (CRC Press, 2018)
Electronic communication and financial transactions have assumed massive proportions today. But they come with high risks. Achieving cyber security has become a top priority, and has become one of the most crucial areas of study and research in IT. This book introduces readers to perhaps the most effective tool in achieving a secure environment, i.e. cryptography. This book offers more solved examples than most books on the subject, it includes state of the art topics and discusses the scope of future research. Preface Overview of Cryptography Introduction Goals of Cryptography Classification of Cryptosystem Practically Useful Cryptosystem Cryptanalysis Basic Algebra Group Ring Field Exercise Number Theory Introduction Prime Numbers Cardinality of Primes Extended Euclidean Algorithm Primality Testing Factorization and Algorithms for it Congruences Quadratic Congruence Exponentiation and Logarithm Discrete Logarithm Problem and Algorithms for it Exercise Probability and Perfect Secrecy Basic Concept of Probability Birthday Paradox Perfect Secrecy Vernam One Time Pad Random Number Generation Pseudo-random Number Generator Exercise Complexity Theory Running Time and Size of Input Big-O Notation Types of algorithm Complexity Classes Exercise Classical Cryptosystems Classification of Classical Cryptosystem Block Cipher Stream Cipher Cryptanalysis of Cryptosystems Exercise